Using Virtual Learning Labs to (Re)Mediate Exclusionary Discipline Practices for Young Children of Color with Disabilities - Kulkarni, Saili; Kim, Sunyoung; Holdman, Nicola (Critical Education, 2024)
Disabled children of color (ages 3-8) face multiple, intersecting oppressions in schools and are more likely to be excluded and/or harshly punished for minor behavioral issues compared to white and/or non-disabled peers. Approaches that center multiple stakeholders (families, teachers, and administrators) using a formative intervention called a Learning Lab (LL) have worked to reduce discipline disparities among secondary and upper primary students of color with disabilities (Bal, 2016). Knowing that discipline disparities can start as early as preschool (Kulkarni et al., 2021), however, we examined how LL (re)mediates exclusionary and harsh discipline practices for young children of color with disabilities. We present qualitative case studies of six California-based stakeholders (four teachers, a parent, and an administrator) who participated in LL sessions virtually from 2021-2022. We share findings and lessons learned from constructing virtual LL spaces to reduce exclusionary and harsh discipline for young children of color with disabilities.